2017
DOI: 10.1177/2167702616671780
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Competing Memories in Substance-Related and Addictive Disorders

Abstract: To maintain an adaptive and flexible behavior, we need to be able to override habitual or inappropriate responses when circumstances require a change in the course of action. This ability, often termed "inhibitory control," is a core cognitive process that is essential to goal-directed behavior. Given the importance of this process, it is not surprising that it has been found to be impaired in a broad range of psychiatric conditions. In particular, inhibitory deficits represent a consistent feature characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…Moreover, a similar pattern has been reported on indirect measures of memory performance (Hertel, Maydon, Ogilvie, & Mor, 2018). The pattern is also consistent with several studies that had similarly related deficient control processes at retrieval with clinical phenomena (e.g., GAD, Kircanski et al, 2016;clinical depression, Groome & Sterkaj, 2008; substance-related and addictive disorders, Stramaccia,Penolazzi,760 Monego, Manzan, Castelli, & Galfano, 2017). More generally, these results are consistent with a recent meta-analysis that associated broader cognitive control deficits with negative thinking (Zetsche, Bürkner, and Schulze, 2018).…”
supporting
confidence: 87%
“…Moreover, a similar pattern has been reported on indirect measures of memory performance (Hertel, Maydon, Ogilvie, & Mor, 2018). The pattern is also consistent with several studies that had similarly related deficient control processes at retrieval with clinical phenomena (e.g., GAD, Kircanski et al, 2016;clinical depression, Groome & Sterkaj, 2008; substance-related and addictive disorders, Stramaccia,Penolazzi,760 Monego, Manzan, Castelli, & Galfano, 2017). More generally, these results are consistent with a recent meta-analysis that associated broader cognitive control deficits with negative thinking (Zetsche, Bürkner, and Schulze, 2018).…”
supporting
confidence: 87%
“…Inhibitory processing underlying RIF has been associated to a range of abilities closely tied to our wellbeing and cognitive efficiency, ranging from working memory to creative problem solving (Nørby, 2015;Storm, 2011). Therefore, it is important to note that it has been found to be impaired in a broad range of disorders traditionally characterized by impulsivity, worry, or rumination (e.g., in obsessive-compulsive disorder, Demeter, Keresztes, Harsányi, Csigó, & Racsmány, 2014; in clinical depression, Groome & Sterkaj, 2010;in schizophrenia, Soriano, Jiménez, Román, & Bajo, 2009;in ADHD, Storm & White, 2010; in substance-related disorders, Stramaccia, Penolazzi, Monego, et al, 2017;in Anorexia Nervosa, Stramaccia, Penolazzi, Libardi, et al, 2017), where alterations of PFC functioning have also been reported. For this reason, there is a great interest in identifying the neural underpinnings of RIF, as well as developing effective strategies to modulate their activity, and clarifying the relationship of the phenomenon with other expressions of cognitive control in different domains.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Stramaccia et al (2017b), we expected patients with GD to exhibit higher scores of self-rated impulsivity than controls. Based on recent evidence showing impairments of different inhibitory components in GD (Kertzman, Vainder, Aizer, Kotler, & Dannon, 2017), and given the similarity of GD and SRD with respect to various inhibitory deficits indexed by response and choice impulsivity (Leeman & Potenza, 2012), we expected a cognitive inhibition impairment in our sample, similar to that reported for patients with SRD (e.g., No€ el et al, 2009;Stramaccia et al, 2017b;Zou, Zhang, Huang, & Weng, 2011). Correlations between task performance and questionnaire scores were expected, with self-report gambling features being mainly associated to inhibitory deficits.…”
Section: Introductionmentioning
confidence: 52%
“…Sixty participants entered the study: 30 outpatients with a diagnosis of GD and 30 healthy control (HC) individuals matched for the most relevant socio-demographic variables (see Table 1). Sample size was based on the study by Stramaccia et al (2017b). Patients were recruited in two mental health services in Northern Italy and diagnosed by a boardcertified attending research team of psychiatrists through the examination of past medical records and a semi-structured interview based on the DSM-IV-TR adapted to the DSM 5.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation